Expresión corporal y su incidencia en el desarrollo de la motricidad gruesa en los niños de 4 años de la escuela de educación básica “la Inmaculada” - Yánez Vega, Jessica Alexandra (2021)
4-year-old children from the "La Inmaculada" elementary school Traditional kindergarten teachers have placed little importance on body language activities with little interest in acquiring knowledge that contributes to these skills. Children's training in the way their bodies move boosts their personal development and training. Lack of movement in children can cause attention deficit, communication with the environment that surrounds them, as well as affecting their psychomotor aspects. According to experts, the gradual and progressive discovery of the body itself, its manifestations that configure the experiences necessary to build children's thinking. The objective of this project is to determine the incidence of corporal expression in the development of gross motor skills in four-year-old children from the “La Inmaculada” Basic Education School, in addition to applying quantitative research techniques and instruments such as the questionnaire of questions applied to the three preschool teachers of the institution as well as an interview with the director. Concluding that there is a lack of knowledge about how to develop body expression as well as little organization to play games, causing children not to develop their gross motor skills, which is very important from birth and in their daily life.